Regulated nuclear import of Rel proteins in the Drosophila immune response. - Wu, L.P.; Anderson, K.V. (Nature, 1998)
The Drosophila immune response uses many of the same components as the mammalian innate immune response, including signalling pathways that activate transcription factors of the Rel/NK-kappaB family. In response to infection, two Rel proteins, Dif and Dorsal, translocate from the cytoplasm to the nuclei of larval fat-body cells. The Toll signalling pathway, which controls dorsal-ventral patterning during Drosophila embryogenesis, regulates the nuclear import of Dorsal in the immune response, but here we show that the Toll pathway is not required for nuclear import of Dif. Cytoplasmic retention of both Dorsal and Dif depends on Cactus protein; nuclear import of Dorsal and Dif is accompanied by degradation of Cactus. Therefore the two signalling pathways that target Cactus for degradation must discriminate between Cactus-Dorsal and Cactus-Dif complexes. We identified new genes that are required for normal induction of transcription of an antibacterial peptide during the immune response. Mutations in three of these genes prevent nuclear import of Dif in response to infection, and define new components of signalling pathways involving Rel. Mutations in three other genes cause constitutive nuclear localization of Dif; these mutations may block Rel protein activity by a novel mechanism.